Health Literacy Disparities: Systemic Barriers and Community Based Interventions for Equitable Healthcare Access - Yusuf , Herlina (Yayasan Sinergi Kawula Muda, 2021)
Health literacy plays a vital role in addressing health disparities and improving healthcare access among marginalized communities. This study explores the relationship between education, economic factors, digital accessibility, and community-based interventions in shaping health literacy levels. A systematic narrative review was conducted, utilizing multiple databases to identify and synthesize relevant literature. The results highlight that higher education levels significantly enhance health knowledge and healthcare engagement, while financial constraints and technological disparities act as barriers to health literacy. Community-based health programs and digital health interventions have shown promise in improving health literacy outcomes, yet systemic challenges persist. This study emphasizes the need for integrated policy approaches that incorporate health education into formal curricula, expand financial support for underserved populations, and improve digital health accessibility. Training healthcare providers in culturally responsive communication strategies is also essential for improving patient-provider interactions. Future research should focus on evaluating long-term intervention outcomes, digital literacy training effectiveness, and interdisciplinary approaches integrating healthcare, education, and technology. Addressing these gaps will contribute to a more inclusive healthcare system, empowering individuals to make informed health decisions and promoting health equity globally.